Artificial Intelligence-Driven Discovery of Magnetic Higher-Order Topological Corner States: A Review From Theoretical Framework to Large-Scale Screening - Liang, Chengtian; Zhu, Zhaoyu; Lin, Yixuan (International Journal of Advanced AI Applications, 2026)
This review explores the integration of artificial intelligence (AI) with condensed matter physics, specifically focusing on the prediction of magnetic higher-order topological corner states. We examine the theoretical foundations of higher-order topological insulators (HOTIs), the unique challenges posed by magnetic systems, and the application of equivariant graph neural networks in high-throughput screening. The article discusses active learning strategies for navigating vast chemical configuration spaces and addresses current limitations regarding data scarcity and strong electronic correlations.